GAMBARAN PENGENDALIAN RISIKO ERGONOMI MUSCULOSKELETAL DISORDERS PADA PEKERJA E-SPORT MOBILE LEGENDS BANG-BANG DI TIM EVOS TAHUN 2023 - Aria Bagus Emirat Faqih, (2024)
Ergonomic risk control to prevent musculoskeletal disorders involves a series of actions designed to reduce the risks that can cause injury to the musculoskeletal system. This study aims to analyze the description of risk control for musculoskeletal disorders in the EVOS Mobile Legends team. This research uses descriptive qualitative methods with in-depth interviews and observations. The research used source triangulation and method triangulation techniques. There are three informants in this study, namely the key informant manager of the EVOS team, the main informant of the workers in the EVOS team, and the supporting informant of the EVOS coach. The results showed that there are several risks to athletes in the EVOS team based on working time and workload. The EVOS team conducts several programs to control risks such as workouts and physiotherapists for athletes in the EVOS team. This was successfully done to reduce ergonomic risks as evidenced by the results of the Nordic Body Map with a low risk level for athletes on the EVOS team. However, changes are needed to the working time applied and adding physical activity to reduce the ergonomic risk of musculoskeletal disorders